Kondisi Fisik dan Teknik Atlet Gulat di Kabupaten Blora - Sarifudin, Ahmad; Setiawan, Ipang (Universitas Negeri Semarang, 2023)
The purpose of this study was to determine the physical condition and technique of wrestling athletes in Blora Regency. The research method uses descriptive quantitative. The instruments used are pretest, and documentation. The subjects of this study were all members of the wrestling athlete club in Blora Regency. The data analysis technique used descriptive statistical techniques. Data analysis by collecting data, reducing data, and presenting data, and drawing data conclusions. The results showed that of the 10 male athletes who were in the good category 5, enough 2, less 3, and less than 1. Meanwhile, of the 4 female athletes who were in the good category 1, enough 2 and less 1. From the results of the physical condition test above The highest score was 553, the lowest was 416, the average score was 500 and SD 37. Meanwhile, for the results of the technical skills test assessment, the following data were obtained from a total of 14 test participants, there was 1 person in the very good category 1, good 4, enough 4, and less than 5, and the standard deviation value is 27 and the average value is 150, so it can be concluded that the physical condition of the wrestling athletes in Blora Regency is in the